Stomach cancer incidence in Brazil: an ecologic study with selected risk factors - Koifman Sergio; Koifman Rosalina Jorge (Cadernos de Saúde Pública, 1997)
Contrary to many industrialized countries in which a sharp decline in stomach cancer incidence has been observed, Brazil still shows intermediate to high incidence rates. An ecologic analysis was performed to explore variables possibly associated with the development of stomach cancer. Cluster analysis, principal component analysis, and factor analysis were carried out with population data, including the following: stomach cancer incidence rates in the early 1990s obtained from population-based cancer registries in Porto Alegre, Campinas, Fortaleza, Belém, and Goiânia; and data from a Brazilian national survey on family expenditures (several diet consumption items and availability of home refrigerators) carried out in 1974-75. The results suggested that past availability of a home refrigerator, i.e. food preservation, may have played an important role in currently observed differences in stomach cancer incidence among the various populations studied in Brazil. Differences in living standards among populations in these cities also appear to have played an important role in the observed incidence differences.